A descriptive analysis of child-relevant systematic reviews in the Cochrane Database of Systematic Reviews - Bow, Simon; Klassen, Jeffrey; Chisholm, Annabritt; Tjosvold, Lisa; Thomson, Denise; Klassen, Terry P; Moher, David; Hartling, Lisa (Université d'Ottawa | University of Ottawa, 2010)
Abstract Background Systematic reviews (SRs) are considered an important tool for decision-making. There has been no recent comprehensive identification or description of child-relevant SRs. A description of existing child-relevant SRs would help to identify the extent of available child-relevant evidence available in SRs and gaps in the evidence base where SRs are required. The objective of this study was to describe child-relevant SRs from the Cochrane Database of Systematic Reviews (CDSR, Issue 2, 2009). Methods SRs were assessed for relevance using pre-defined criteria. Data were extracted and entered into an electronic form. Univariate analyses were performed to describe the SRs overall and by topic area. Results The search yielded 1666 SRs; 793 met the inclusion criteria. 38% of SRs were last assessed as up-to-date prior to 2007. Corresponding authors were most often from the UK (41%). Most SRs (59%) examined pharmacological interventions. 53% had at least one external source of funding. SRs included a median of 7 studies (IQR 3, 15) and 679 participants (IQR 179, 2833). Of all studies, 48% included only children, and 27% only adults. 94% of studies were published in peer-reviewed journals. Primary outcomes were specified in 72% of SRs. Allocation concealment and the Jadad scale were used in 97% and 25% of SRs, respectively. Adults and children were analyzed separately in 12% of SRs and as a subgroup analysis in 14%. Publication bias was assessed in only 14% of SRs. A meta-analysis was conducted in 68% of SRs with a median of 5 trials (IQR 3, 9) each. Variations in these characteristics were observed across topic areas. Conclusions We described the methodological characteristics and rigour of child-relevant reviews in the CDSR. Many SRs are not up-to-date according to Cochrane criteria. Our study describes variation in conduct and reporting across SRs and reveals clinicians' ability to access child-specific data.